Low Impact of Nitrogen Fertilization on Grafted Tomatoes under High-tunnel Production - Maria-Sole Bonarota; Felipe H. Barrios-Masias (HortTechnology)
High-tunnel systems can improve and prolong production under challenging climate, but research on nitrogen management and grafting is still needed. This study analyzes the effects of rootstock and two N fertilization levels in northern Nevada under high-tunnel commercial production. We report on tomato yield, growth, leaf nutrient profile, and spectral indices [i.e., soil plant analysis development (SPAD) and normalized difference vegetation index (NDVI)] correlation with leaf nitrogen. Although rootstock influenced yield and leaf nutrient profile depending on location, no clear effect from the nitrogen fertilization was observed in growth and yield. Moreover, the low accuracy of SPAD and NDVI indices in predicting leaf nitrogen status undermined the capacity to provide enough support for a sustainable nitrogen fertilization management.